Kraujavimas iš peptinės opos Baltarusijoje - Lobankov, Vladimir M. (Lietuvos chirurgija, 2006)
Vladimir M. Lobankov Gomel State Medical University, Department of Hospital Surgery, Lange str. 5, 246000 Gomel, Belarus E-mail: lobankov1959@mail.ru Background / objective The aim of the present paper is a multilevel quantitative review of urgent operations due to peptic ulcer bleeding in Belarus. Methods We reviewed the statistics of the Public Health Ministry of the Republic of Belarus to determine the absolute number of surgical interventions in the regions and in Minsk during 1990 to 2004. Individually for the Gomel region, the similar statistics of the Regional Health Department were analyzed since 1980. It is noteworthy that before 1990, interventions due to ulcer bleeding were ignored in the reports of Ministry for Health of the USSR and of the Republics. With the account of demographic changes, the relative annual frequency of relevant operations was determined per 100,000 inhabitants. The analysis includes also the dynamics of surgeries for ulcer bleeding during 1990–2004. Results Since the early 90s, a distinct rise of urgent operations for ulcer bleeding amounted to 1.5–2.0 and more times in Belarus. Since the second half of the 90s, the number of operations stabilized relatively at a level of 10–12 interventions per 100,000 annually. The number of hospitalizations with ulcer bleedings reached 60 per 100,000 and tends to grow. Conclusions The number of operations for ulcer bleeding tends to reduce in the recent years due to extensive implementation of conservative methods of hemostasis rather than to reduction of bleedings proper. Key words: bleeding gastroduodenal ulcers, urgent operations, surgical activity